Pengaruh Konten Media Sosial dan Fear of Missing Out (FoMO) terhadap Kepekaan Sosial Siswa - Ana Dhafarikhah; Chr. Argo Widiharto; Venty Venty (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
This study aimed to determine the influence of social media content and Fear of Missing Out (FoMO) on social sensitivity among eleventh-grade students at SMA Negeri 10 Semarang. This research employed a quantitative approach with a correlational design. The population consisted of 319 students, while the sample included 98 students selected using an accidental sampling technique. Data were collected using questionnaires and Likert scales, including a social media content questionnaire, a social sensitivity scale, and a Fear of Missing Out (FoMO) scale. Data analysis was conducted using multiple linear regression analysis through SPSS. The results showed that social media content had a positive and significant effect on students’ social sensitivity, with a significance value of 0.000 < 0.05 and a t-value of 8.170 > 1.98525. Meanwhile, Fear of Missing Out (FoMO) did not have a significant effect on students’ social sensitivity, with a significance value of 0.348 > 0.05 and a t-value of –0.942 < 1.98525. Simultaneously, social media content and Fear of Missing Out (FoMO) significantly influenced students’ social sensitivity, with a significance value of 0.000 < 0.05 and an F-value of 33.395 > 3.09. The coefficient of determination (R Square) of 0.413 indicated that both variables contributed 41.3% to students’ social sensitivity. This study demonstrates that social media content has a more dominant influence on social sensitivity compared to Fear of Missing Out (FoMO).